2015
DOI: 10.17531/ein.2015.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and model studies on the influence of the run flat tire damage on braking dynamics of the multi-axial special purpose vehicle

Abstract: Article citation info: (*) Tekst artykułu w polskiej wersji językowej dostępny w elektronicznym wydaniu kwartalnika na stronie www.ein.org.pl Prochowski L, wAch w, JAckowski J, Pieniążek w. experimental and model studies on the influence of the run flat tire damage on braking dynamics of the multi-axial special purpose vehicle. eksploatacja i niezawodnosc -Maintenance and reliability 2015; 17 (1): 118-128. Leon Prochowski wojciech wAch Jerzy JAckowski wiesław PieniążekExpErimEntal and modEl studiEs on thE infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…To begin with, the greatest challenge comes from vehicle system stability control, which covers the lateral and longitudinal stability control for the vehicle with tire blowout in the freeway. As the fundamental performance, vehicle lateral stability control has been widely investigated via applying conventional electronic stability program and lane keeping control techniques; see Blythe et al (1998); Prochowski et al (2015); Tandy et al (2013); Bäcker et al (2017); Jin et al (2018); and Wang et al (2016a). For example, Bäcker et al (2017) reported a simulation case to imitate a tire inflation pressure loss and its consequences for the vehicle stability, and electric stability controller was designed to assure vehicle lateral stability after tire blowout.…”
Section: Introductionmentioning
confidence: 99%
“…To begin with, the greatest challenge comes from vehicle system stability control, which covers the lateral and longitudinal stability control for the vehicle with tire blowout in the freeway. As the fundamental performance, vehicle lateral stability control has been widely investigated via applying conventional electronic stability program and lane keeping control techniques; see Blythe et al (1998); Prochowski et al (2015); Tandy et al (2013); Bäcker et al (2017); Jin et al (2018); and Wang et al (2016a). For example, Bäcker et al (2017) reported a simulation case to imitate a tire inflation pressure loss and its consequences for the vehicle stability, and electric stability controller was designed to assure vehicle lateral stability after tire blowout.…”
Section: Introductionmentioning
confidence: 99%